Development of a variance model for the prediction of water absorption and thickness swelling for an experimental design pvc reinforced composite pipes - Orhorhoro, Ejiroghene Kelly; Tamuno, Rogers Ibunemisam; Chukwuedo, Azuka Joses (Applied Research and Smart Technology (ARSTech), 2023)
Water absorption is a significant constraint encountered when NFs reinforce polymer matrices. It is the primary cause of the breakdown of the fibre-matrix interface, resulting in swelling of the fibres, loss in the efficiency of load transfer between the matrix and the fibres, and ultimately a reduction in the strength and stiffness of the composites. This study investigated the development of a variance model for predicting water absorption and thickness swelling for an experimental design of Polyvinyl chloride (PVC) reinforced composite pipes. The quadratic model was used to model the influence of the process factors (independent variables) on the responses (i.e., water absorption and thickness swelling). Statistical analysis of the experimental data was carried out by fitting the chosen quadratic model to the data to estimate the unknown model parameters. The results revealed that the model was characterised by a high R2 value, indicating a perfect fit between the experimental observations and model predictions. The value of the variation coefficient was 3.320, which means the high precision and reliability of the model. The results of water absorption tests as a function of independent process factors showed that increasing the level of PVC in the composite material resulted in a decrease in the water absorption capacity of the material. This is desirable since an excellent composite pipe material should resist moisture intrusion.